The failure of child support : gendered systems of iInaccessibility, inaction and irresponsibility - Cook, Kay (Bristol : Policy Press, 2022)
Drawing on interviews with key international informants across sixteen countries, this book examines how child support systems often fail to transfer payments from separated fathers to mothers and their children. It identifies how the gender order is entrenched through child support failure and offers possibilities for feminist reform.
Title from publisher's bibliographic system (viewed on 10 Oct 2022).
Keywords: Child support -- Government policy -- Cross-cultural studies; Sex role -- Political aspects -- Cross-cultural studies; Single mothers -- Cross-cultural studies